2015
DOI: 10.1002/pbc.25607
|View full text |Cite
|
Sign up to set email alerts
|

Detection and role of minimal disseminated disease in children with lymphoblastic lymphoma: The AIEOP experience

Abstract: Our data demonstrated that MDD studied at diagnosis by MFC could represent a useful prognostic tool in childhood LBL and further application for better stratification is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
(82 reference statements)
2
25
0
1
Order By: Relevance
“…MDD was detected in 49% (32/65) of BM samples, whereas only 21% (14/65) were positive at standard morphological evaluation. Using an MDD cut‐off level of 3% by FCM, the 5‐year EFS was 60% for patients with MDD >3% LBL cells versus 83% for the remaining patients ( P = 0·04) (Mussolin et al , ). Additional prospective trials are needed to determine the level of significant MDD and the role of BM MRD in paediatric T‐LBL as prognostic markers.…”
Section: Prognostic Parameters Recurrent Genetic Alterations and Rismentioning
confidence: 99%
“…MDD was detected in 49% (32/65) of BM samples, whereas only 21% (14/65) were positive at standard morphological evaluation. Using an MDD cut‐off level of 3% by FCM, the 5‐year EFS was 60% for patients with MDD >3% LBL cells versus 83% for the remaining patients ( P = 0·04) (Mussolin et al , ). Additional prospective trials are needed to determine the level of significant MDD and the role of BM MRD in paediatric T‐LBL as prognostic markers.…”
Section: Prognostic Parameters Recurrent Genetic Alterations and Rismentioning
confidence: 99%
“…One study found that the 2-year EFS was shorter in children with minimal disseminated disease in the bone marrow ($1% T-LBL cells) than in those without (68.1% 6 11.1% vs. 90.7% 6 4.4%, p 5 0.031) [66]. Similarly, a recent Italian series of 52 children with T-LBL found that the 5-year EFS was shorter for patients with O3% LBL cells in the bone marrow than for patients below this cutoff (60.0% 6 22% vs. 83.0% 6 6%, p 5 0.049) [67]. Minimal residual disease status has been successfully used to select high-risk adult LBL patients for SCT [35].…”
Section: Minimal Disseminated Disease and Residual Diseasementioning
confidence: 87%
“…In the future, FC may play an important role also in patients with existing mature B‐cell lymphomas by identifying low‐level B‐LBL cells in peripheral blood or bone marrow cells , which could be evaluated for IgH/BCL2 and “double hit” cytogenetic abnormalities. Early identification of these cells may herald an impending transformation of an existing or previously treated lymphoma and enable an early therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%